A buckling model for the stability design of steel columns with intermediate gravity loads. (February 2016) - Teh, Lip H.; Gilbert, Benoit P.
Abstract: This paper points out an accurate buckling model for determining the flexural effective length of a steel column subjected to intermediate gravity loads, for applications in the 2D second-order elastic analysis based design procedure. The proposed buckling model has "notional" horizontal restraints where equivalent horizontal forces have been applied, and can be readily programmed into a structural analysis/design software. Thirty columns having various end restraints and subjected to concentrated gravity loads within their unsupported lengths are analysed to demonstrate the merits of the proposed buckling model. It is shown that, in most of the cases analysed, the proposed buckling model leads to more liberal column capacities compared to the use of the unity effective length factor or the buckling model described in the European drive-in rack design code. The more liberal capacities are very close to the ultimate loads determined through second-order plastic-zone analysis. Highlights: Buckling model for the effective length of a column subject to intermediate loads Accurate and economical elastic analysis based design procedure Explains the implication of the notional horizontal loads Resolves doubt concerning the effective length factor equal to unity